2016
DOI: 10.1155/2016/1846296
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Pretreatment at GB20 Exerts Antinociceptive Effects via Peripheral and Central Serotonin Mechanism in Conscious Migraine Rats

Abstract: Background. While electroacupuncture (EA) pretreatment in migraine has been found to attenuate pain and frequencies of attacks, the underlying mechanism of its antinociceptive effect remains poorly understood. Emerging evidence suggests that the serotonin system may be involved in migraine pathophysiology. Method. Forty male Sprague-Dawley rats were randomly assigned to Control, Model, EA, and sham acupuncture (SA) groups. HomeCageScan was used to measure the effects on spontaneous nociceptive behaviors. Radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…In previous studies, a reduction of 5-HT in plasma was found in a rat model of migraine and an increase in serum NE was observed in climacteric depression after EA treatment. 17,18 Therefore, it could be inferred that EA therapy may improve symptoms of anxiety and depression by regulating the secretion of neurotransmitters such as NE and 5-HT. These findings should be interpreted with caution, however, given these parameters were all secondary outcomes that were added post-hoc to the original trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, a reduction of 5-HT in plasma was found in a rat model of migraine and an increase in serum NE was observed in climacteric depression after EA treatment. 17,18 Therefore, it could be inferred that EA therapy may improve symptoms of anxiety and depression by regulating the secretion of neurotransmitters such as NE and 5-HT. These findings should be interpreted with caution, however, given these parameters were all secondary outcomes that were added post-hoc to the original trial.…”
Section: Discussionmentioning
confidence: 99%
“…16 Acupuncture treatment has also been shown to increase serum levels of NE in climacteric depression. 17 Plasma levels of 5-HT decreased after EA in a rat model of migraine, 18 and plasma AD was found to be increased in anaesthetised patients given EA before surgery. 19 Moreover, an increase in serum GABA was found after EA for spastic paralysis after stroke.…”
Section: Introductionmentioning
confidence: 96%
“…This process can be reversed by 5-HT1 and 5-HT3 antagonists. Headache relief was considered to be primarily engendered by an increase in serotonin release in the medulla and TNC regions [ 57 , 58 ]. Serotonin could inhibit inflammatory and neuropathic pain more effectively at 2–10 Hz than at 100 Hz [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Jumping interrupts other states like walking); (3) resting behavior (the rat rests with hardly any movement; either sits or lies down, which includes sleeping. Apparently, no interest in the environment); and (4) grooming behavior (the rat grooms snout, head, fur, or genitals including scratching and licking of paws during a grooming session) [2629]. The total time spent engaging in the behavior was calculated in the present study.…”
Section: Methodsmentioning
confidence: 99%